Safe, effective and appropriate prescribing of anticoagulant therapies. (2nd April 2019) - Khan, Nazish
Abstract : Anticoagulation can be prescribed for numerous indications. Some examples include stroke prevention in the context of non-valvular atrial fibrillation; thromboprophylaxis following mechanical heart valve replacement and orthopaedic surgery; prevention and treatment of deep vein thrombosis/pulmonary embolism; and the prevention of arterial thrombosis in patients who present following an acute coronary syndrome. The armamentarium of anticoagulant therapy has evolved considerably over the last decade with the introduction of several new agents. This article will provide an overview of the mechanism of action for each agent, in addition to its place in therapy, contra-indications, cautions for use and the monitoring requirements that should be considered to ensure safe, effective and appropriate prescribing of anticoagulant therapies